Unaturlige fortællinger. Hinsides mimetiske modeller - Alber, Jan; Iversen, Stefan; Nielsen, Henrik Skov; Richardson, Brian (K&K - Kultur og Klasse, 2011)
UNNATURAL NARRATIVES, UNNATURAL NARRATOLOGY | In recent years, the study of unnatural narrative has developed into one of the most exciting new paradigms in narrative theory. Both younger and more established scholars have become increasingly interested in the analysis of unnatural texts, many of which have been consistently neglected or marginalized in existing narratological frameworks. By means of the collaboration of four scholars who have been developing unnatural narratology, this article seeks to summarize key principles, to consolidate some conclusions, to extend the work through carefully chosen examples, and, finally, to point toward the future.